2015
DOI: 10.1111/jcpt.12285
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of 4-hydroxybenzoic acid ester with glycerol

Abstract: A novel hydrophilic analogue of parabens was synthetized and tested for its antimicrobial activity against selected microorganisms in model system. This study confirms antimicrobial potential of 1-O-(4-hydroxybenzoyl)-glycerol, which is comparable with other commercially used parabens. Unlike commercial parabens, it is possible to expect more significant antimicrobial activity of 1-O-(4-hydroxybenzoyl)-glycerol in real emulsion systems due to the increased solubility of this substance in water phase and also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
(35 reference statements)
0
20
0
1
Order By: Relevance
“…; Kosová et al . ). Increased expression of both hypoxanthine and tricarballylate in LP+RBE suggested that RBE modulations to L. paracasei nucleotide and TCA cycle metabolism are important to its S .…”
Section: Discussionmentioning
confidence: 97%
“…; Kosová et al . ). Increased expression of both hypoxanthine and tricarballylate in LP+RBE suggested that RBE modulations to L. paracasei nucleotide and TCA cycle metabolism are important to its S .…”
Section: Discussionmentioning
confidence: 97%
“…Other metabolites from this study that varied by cultivar, and that should be considered for importance to human health, were 4-hydroxybenzoate and salicylate. The 4-hydroxybenzoate had a higher relative abundance in Rang Jay (grown in Cambodia), and this compound has established antimicrobial properties [62,74], as well as antioxidant [75] actions. Salicylate, a phytochemical with a broad function in plant growth and development [76], is also an active component of aspirin, and it has well-documented anti-diabetic, anti-inflammatory, and cardio-protective properties [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Other metabolites from this study that varied by cultivar and should be considered for importance to human health were 4-hydroxybenzoate and salicylate. The 4-hydroxybenzoate had a higher relative abundance in Rang Jay (grown in Cambodia), and this compound has established antimicrobial properties [62,74] as well as antioxidant [75] actions. Salicylate, a phytochemical with a broad function in plant growth and development [76], is also an active component of aspirin and has well-documented anti-diabetic, anti-inflammatory, and cardio-protective properties [77,78].…”
Section: Discussionmentioning
confidence: 99%